USING MONOSODIUM GLUTAMATE (MSG) AS A MEASURE TO REDUCE SALT INTAKE – AN EFFECTIVE APPROACH TO PREVENT SOME NON-COMMUNICABLE DIASEAS (Vietnam Journal of Community Medicine, 2022)
Objective: The aims of this study were to review methods for salt intake reduction, and explore the possibility of using monosodium glutamate (MSG) as an effective way to reduce salt intake.Methods: Using literature review method gathering relevants documents, papers, books related to the research topics.Results: Reducing salt intake has been recommended by World Health Organization as a measure to prevent and control non-communicable diseases. Suggested ways to reduce salt intake include consumer-friendly nutrition-labelling regulations, health education for the community, reduce salt gradually, and reduce salt ammount during cooking. MSG is a safe food additive which has proved by many international health organizations. Using MSG in cooking can be an effective measure to reduce salt but remain keeping the flavor of the dishes.Conclusion: There are several measures to reduce salt intake. Using MSG in cooking meals can be an effective way to remain diets with salt intake reduction.
Keywords: Salt intake reduction, monosodium glutamte, MSG, reduced salt meals.